Challenges Facing Women Survivors of Self-Immolation in the Kurdish Regions of Iran: A Qualitative Study - Yoosefi Lebni, Javad; Abbas, Jaffar; Khorami, Farhad; Khosravi, Bahar; Jalali, Amir; Ziapour, Arash (Frontiers in Psychiatry, 2020)
Women confront many problems after self-immolation, so the purpose of this study was to explore the challenges of women returning to normal life after self-immolation. This study was conducted with qualitative approach and conventional content analysis. Data were collected through semi-structured interviews with 19 Kurdish women who attempted self-immolation in Iran. They were sampled through purposeful sampling and snowball sampling. The Lincoln and Guba criteria were used to strengthen the research. The results of data analysis were categorized into 5 main categories including: 1-psychological problems 2- lack of social and legal supportive structures 3- incomplete treatment 4-poor self-care 5- social problems. These categories consist of 19 subcategories. Having been rescued from self-immolation, the women confront many challenges to return to normal life. Reducing these women’s problems and paving the way for their return to life require multi-dimensional and community-based interventions. Therefore, all social organizations and institutes should cooperate and each of them paves part of the way.